التّظاهرات الرّئوية لدى مرضى الدّاء الرّثياني - الدوّ, كاسر; الخيّر, محمد; بوّاط, نفّات (Latakia University Journal -Medical Sciences Series, 2019)
الداء الرثياني هو مرض جهازي مزمن له تظاهرات رئوية متعددة، وإن شدة هذه التظاهرات تتعلق بشدة ومدة الإصابة بالداء الرثياني. أجرينا دراسة شملت 52 مريضاً بداءٍ رثياني لتشخيص التظاهرات الرئوية، بالاعتماد على القصة المرضية والفحص السريري، الصورة الشعاعية البسيطة للصدر، الطبقي المحوري للصدر، اختبارات وظائف الرئة، وجدت التظاهرات الرئوية لدى %46 من مرضى الدراسة، وتوزعت على الشكل التالي: 21%داء رئوي خلالي . %9.6 انسداد بالطرق التنفسية الصغيرة. %7.6 انصباب جنب. %7.6 عقيدات رثيانية . %5.7 توسع قصبات. %8.3 فرط التوتر الرئوي الثانوي. Rheumatoid arthritis is a chronic multi-system disease with different pulmonary manifestations. The severity of these manifestations varies in accordance with the severity and duration of RA. We studied 52 patients with RA to assess if there were any lung disease depending on history and clinical examination, chest X ray, chest computed tomography, lung functions tests, and arterial blood gases. Pulmonary manifestations were identified in 46% of patients; and they were as follows: Interstial lung disease21%. Small airway obstruction 9.6 %. Pleural-effusion7.6%. Rheumatoid nodules.5.7%. Bronchiectasis5.7%. Pulmonary hypertension 3.8%